Mechanisms of the Learning Impact of Teacher-Organized Online Schoolwork Sharing Among Primary School Students. (September 2020) - Lai, Chun; Wen, Yun; Gao, Tian; Lin, Chin-Hsi
Despite the increasing amount of literature on the educational potential of social media for learning, little is understood about how different functions of social media might affect learning in the K-12 context, the primary school education context in particular. This study examined the effect on learning of a key function of social media—online sharing. It examined how teacher-organized online schoolwork sharing on a social media-based platform, Seesaw, influenced a group of primary school students' learning. Survey responses from 337 primary school students revealed that students had positive perceptions of the impact of schoolwork sharing on learning. Structural equation modeling analysis of the survey responses revealed that online schoolwork sharing influenced individual student learning primarily through enhanced perceptions of the value of online sharing for learning from peer review, which influenced learners' efforts in schoolwork. Efforts in schoolwork then positively influenced students' self-efficacy in learning. The findings suggest that primary school teachers should actively utilize the sharing function of social media to facilitate student learning. The findings also underscore the importance of enhancing peer review and students' perceptions of its value in order to maximize the learning potential of online schoolwork sharing for primary school students.